Integrasi Penginderaan Jauh Dan Sistem Informasi Geografis Dalam Evaluasi Lahan Untuk Permukiman Di Kota Cilacap - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT Basically, this research refers to land evaluation using Color Panchromatic Aerial Photograph of Cilacap City flown in 1999 and scaled 1 : 20.000 as data source, and geographical information system (GIS) as a tool in data collecting, processing and analyses. Therefore, beside to find out land suitability for settlement, the objectives of this research are to find out the accuracy of the result. n this research, land characteristics were obtained by interpreting aerial photograph and completed by field work and laboratory analyses. The thematic maps were made by integrating remote sensing and GIS, i.e. digitizing on screen with controlled aerial photo mosaic as the backdrop. The method used in land evaluation was parametric one. In this method, scores were platted to individual land characteristics and suitability indices were calculated using three suitability models, i.e. physical suitability model, suitability model of land use conversion and land accessibility, and settlement suitability model. To make evaluation result would be in accordance with the government policy, the result was adjusted to detail spatial arrangement plan. The results of this research are: parameter accuracy for Iandform is 77,77%, parameter accuracy for land use is 86.36%, average of mapping accuracy for landform is 84,91%, and average of mapping accuracy for land use is 83,13%. The inaccuracy was influenced by low contrast ratio, high complexity of environment in urban side, photo scale and interpreter's knowledge limitedness. The accuracy of evaluation result which was obtained by comparing the result with detail spatial arrangement plan is insufficient. The geometric error of aerial mosaic photograph which was used to make the thematic maps is 12,58 meters. The result of land evaluation indicates was only 89,67 hectares or 1,94% of 4.626,04 hectares land in Cilacap, are suitable (S1) for settlement, and only 5,09 hectares are planned for settlement by government. The amount of moderately suitable land (52), marginally suitable land (53), currently not suitable land (Ni) and permanently not suitable land (N2) which was planned for settlement, are 1.094,99 hectares, 761,41 hectares, 143,14 hectares and 292,14 hectares. The result of land evaluation also indicates that land suitability is not in accordance with 1986/1987 - 2003/2004 Detail Spatial Arrangement Plan of Cilacap Administrative City, therefore a plan revision is recommended.